2018
DOI: 10.1016/j.mjafi.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of near infrared spectroscopy as screening tool for detecting intracranial hematomas in patients with traumatic brain injury

Abstract: Near Infra Red Spectroscopy (NIRS) is a good screening tool for prediction of intra cerebral haemorrhage in the field and even intensive care units. This was the first study of its kind in the Indian subcontinent and the results suggest that NIRS is a good device to predict intracranial subdural and epidural haematomas. It is however not superior to computer tomography and magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…A report from New Delhi, India, demonstrated that non-contrast CT is an effective screening tool for predicting ICH in emergency situations and intensive care units, outperforming Near Infra-Red Spectroscopy (NIRS) which is unreliable for sub-acute to chronic hemorrhage and bilateral lesions (14). In Japan, CT is predominantly used for post-trauma ICH evaluation and provides essential information about brain structure, similar to the findings of this study (15).…”
Section: Discussionsupporting
confidence: 67%
“…A report from New Delhi, India, demonstrated that non-contrast CT is an effective screening tool for predicting ICH in emergency situations and intensive care units, outperforming Near Infra-Red Spectroscopy (NIRS) which is unreliable for sub-acute to chronic hemorrhage and bilateral lesions (14). In Japan, CT is predominantly used for post-trauma ICH evaluation and provides essential information about brain structure, similar to the findings of this study (15).…”
Section: Discussionsupporting
confidence: 67%
“…NIRS is a method that has been studied by various clinics for its success in showing cerebral tissue oxygenation and is successful in different intracranial events ( 10 , 11 ). Although CT and magnetic resonance imaging are still the gold standard in cases of headache with suspected brain hemorrhage or infarction according to the literature, NIRS is used as an auxiliary and monitoring test between these devices as it provides less information ( 14 , 15 ). However, there are insufficient studies regarding its diagnostic value in suspicious intracranial events in EDs.…”
Section: Discussionmentioning
confidence: 99%